PAHs-induced metabolic aberrations and intact circadian rhythms in zebrafish: a promising approach for aquatic surveillance - Meng Chen; Senmei He; Zongming Ren (Scientific Reports)
Abstract Polycyclic aromatic hydrocarbons (PAHs), recognized as teratogenic and carcinogenic pollutants, exhibit moderate-to-high acute toxicity and long-term detrimental effects on aquatic organisms. However, conventional monitoring methods often fail to detect early-stage sublethal impacts of PAHs, potentially due to limited disruption of intrinsic circadian rhythms during initial exposure periods. To investigate the physiological responses of aquatic species to PAHs, we employed real-time biomonitoring to evaluate metabolic alterations in juvenile zebrafish (Danio rerio), including oxygen consumption rate (OR), carbon dioxide excretion rate (CR), ammonia-nitrogen excretion rate (AE), respiratory quotient (RQ), and ammonia quotient (AQ), alongside their circadian rhythmicity under PAH exposure. Two representative PAHs, phenanthrene (Phe) and pyrene (Pyr), were tested at 10%×LC50(96 h) concentrations (Phe: 102 µg/mL; Pyr: 70.6 µg/mL) over a 7-day exposure period. Comparative analysis revealed significant PAH-induced suppression of OR and CR, while AE was markedly enhanced, resulting in elevated RQ and AQ. Despite these metabolic responses, circadian rhythms remained intact across all parameters. These findings indicate that PAHs induce transient metabolic dysregulation without perturbing core circadian mechanisms, highlighting the feasibility of zebrafish metabolic profiling as a sensitive tool for aquatic PAH monitoring.